Variability for resistance to fall armyworm in Guadeloupe among maize populations improved for resistance to various insects - Welcker, C.=700 1 Clavel, D.; Gilet, J.D.; Felicite, F.; Guinet, I.
Sumario (En)
Ilus.; 15 ref.
Keywords: ZEA MAYS; RESISTENCIA A LAS PLAGAS; SPODOPTERA FRUGIPERDA; INSTITUCIONES DE INVESTIGACION; VARIACION GENETICA